2009 IEEE International Ultrasonics Symposium 2009
DOI: 10.1109/ultsym.2009.5441683
|View full text |Cite
|
Sign up to set email alerts
|

Stacked crystal resonator: A highly linear BAW device

Abstract: Besides small size, exceptional insertion loss and outstanding isolation, bulk acoustic wave (BAW) filters and duplexers are often the preferred choice in the transmit path of mobile frontend due to their excellent power handling capabilities. However, they exhibit a nonlinear behavior, causing generation of higher harmonics and a sensitivity of the resonance frequency towards a DC voltage bias. In this paper we present a new BAW device, a stacked crystal resonator (SCR), which intrinsically cancels out the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Suppression of nonlinear signal generation in RF SAW and BAR devices is one of the most important subjects on the RF front end in recent cellular handsets. [22][23][24][25][26][27][28][29][30][31][32][33][34] Especially, the issue of second-order nonlinear products of BAR is well known. 22) In a standard FBAR consisting of piezoelectric AlN and top and bottom electrodes, several detailed investigations [31][32][33][34] have shown that the piezoelectric AlN is the dominant material contributing to the second-order nonlinear response.…”
Section: Introductionmentioning
confidence: 99%
“…Suppression of nonlinear signal generation in RF SAW and BAR devices is one of the most important subjects on the RF front end in recent cellular handsets. [22][23][24][25][26][27][28][29][30][31][32][33][34] Especially, the issue of second-order nonlinear products of BAR is well known. 22) In a standard FBAR consisting of piezoelectric AlN and top and bottom electrodes, several detailed investigations [31][32][33][34] have shown that the piezoelectric AlN is the dominant material contributing to the second-order nonlinear response.…”
Section: Introductionmentioning
confidence: 99%
“…Suppression of nonlinear signal generation in RF SAW/ BAW devices is one of the most important subjects concerning RF front-end modules in recent cellular handsets. [22][23][24][25][26][27][28][29][30][31][32][33][34] In particular, issues with second-order nonlinear products of BAWs are well known. 22) Therefore, clarification of nonlinear signal generation mechanisms in SAW/BAW devices is urgently required.…”
Section: Introductionmentioning
confidence: 99%
“…Linearity is one of the biggest research topics for RF SAW/ BAW duplexers and/or multiplexers, [1][2][3][4][5][6][7][8][9][10][11][12] and accurate and fast simulation tools are highly demanded for further suppression of nonlinear signal generation in these devices.…”
Section: Introductionmentioning
confidence: 99%